Role of Animal Models in Parkinson's Disease (PD): What Role They Play in Preclinical Translational Research - Srivastava, Rajnish; Dilnashin, Hagera; Kapoor, Devesh; Aparna, Sai; Heidarli, Elmira; Singh, Surya P.; Jain, Vivek (CNS & Neurological Disorders - Drug Targets, 2024)
Background: Animal models for drug discovery and development in Parkinson ’s disease have played an important role in the characterization of the pathophysiology of diseases and associated mechanisms of injury, drug target identification, and evaluation of novel therapeutic agents for toxicity/ safety, pharmacokinetics, pharmacodynamics, and efficacy. Objective: The review is intended to reform the scope, advantages, and limitations of various Parkinson’s Disease models and their scope in translational research. The lack of a gold standard for PD animal models presents a major challenge in devising a validation system. This review is an attempt to provide a way to adopt the validation approach for PD animal model for research. Methods: Because underlying disease mechanisms are so similar across species, it is possible to extrapolate results from Parkinson's disease studies using animal models. Furthermore, behavioural tests used to access the neurobehavioral test with its limitations were explored for rodents, non-human primates, lower-order animals, and invertebrates. The role of gender selectivity and non-selectivity is the one major concern in PD model validation that is addressed in the review. Results: The rigorous validation has been done on animal models for Parkinson's disease (PD) based on comparisons to the human state. Regarding toxicological and safety investigations in PD, non-animal options must be thoroughly validated. There are both advantages and disadvantages to using animal models of Parkinson's disease as proof-of-concept research. Conclusion: The specific animal model selected for a given drug to be tested and developed depends on the goal of the specific study.
Keywords: validation